MQUIT (Game Money) / Wan Noor Faaizah Wan Omar ... [et al.] - Wan Omar, Wan Noor Faaizah; Chek Sidik, Noreha; Bakri, Mohd Ikmal Hakim; Nasir, Muhamad Izwan (Universiti Teknologi MARA, Kedah, 2018)
"mQuit Interactive Game" is an interactive type of game concept inspired from monopoly . It is suitable for of all users regardless of age and gender by providing knowledge and awareness in an effort to creating a non-smoking environment.